A new case of autosomal recessive agammaglobulinaemia with impaired pre-B cell differentiation due to a large deletion of the IGH locus - Milili, M; Antunes, H; Blanco-Betancourt, C; Nogueiras, A; Santos, E; Vasconcelos, J; Castro e Melo, J; Schiff, C (Springer, 2002)
Males with X-linked agammaglobulinaemia (XLA) due to mutations in the Bruton tyrosine kinase gene constitute the major group of congenital hypogammaglobulinaemia with absence of peripheral B cells. In these cases, blockages between the pro-B and pre-B cell stage in the bone marrow are found. The remaining male and female cases clinically similar to XLA represent a genotypically heterogeneous group of diseases. In these patients, various autosomal recessive disorders have been identified such as mutations affecting IGHM, CD79A, IGLL1 genes involved in the composition of the pre-B cell receptor (pre-BCR) or the BLNK gene implicated in pre-BCR signal transduction. In this paper, we report on a young female patient characterised by a severe non-XLA agammaglobulinaemia that represents a new case of Igmu defect. We show that the B cell blockage at the pro-B to pre-B cell transition is due to a large homologous deletion in the IGH locus encompassing the IGHM gene leading to the inability to form a functional pre-BCR. The deletion extends from the beginning of the diversity (D) region to the IGHG2 gene, with all JH segments and IGHM, IGHD, IGHG3 and IGHG1 genes missing. CONCLUSION: alteration in Igmu expression seems to be relatively frequent and could account for most of the reported cases of autosomal recessive agammaglobulinaemia.
Keywords: Agamaglobulinemia; Deleção Cromossómica; Genes de Imunoglobulinas; Glicoproteínas de Membrana